Faith and learning on the edge: a bold new look at religion in higher education - Claerbaut, David (Zondervan, 2025)
Christian education or baptized paganism? -- The artificial lighting of the academic mainstream -- The relatives of naturalism -- Down the intellectual cul de sac of postmodernism -- The high stakes politics of the academic mainstream -- How does Christian scholarship fit into the academic mainstream? -- What is faith and learning? -- How can we be true to the role of learning in Christian scholarship? -- Where does reason end and faith begin? -- What are the components of faith and learning? -- Interpassage : stimulating the dialogue -- Why is creation central to the faith-and-learning enterprise? -- What is the mind-set of the Christian in the physical sciences? -- Christian implications in the physical sciences -- How do we look at art through Christian eyes? -- Some guidelines for the Christian artist -- How do we teach literature in a postmodern world? -- Philosophy under a Christian lens -- Atheist vs. Christian : Freud and Lewis debate the great philosophical questions -- Education, the battleground -- What is a Christian historian? -- Reflections for the Christian political scientist -- Psychology : need theory, a place where faith meets learning -- Faith meets the mental health models -- Sociology : faith in the eye of naturalism -- Economics : some Christian views on the "dismal" science -- Conclusion